2021
DOI: 10.1007/s10654-021-00792-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index, its change and cognitive impairment among Chinese older adults: a community-based, 9-year prospective cohort study

Abstract: Objective To examine the association of baseline body mass index (BMI) and BMI change with cognitive impairment among older adults in China.Methods The study included data from the Chinese Longitudinal Healthy Longevity Study, a national community-based prospective cohort study from 2002-2018. Baseline BMI and BMI change measurements were available for 12,027 adults aged older than 65 years. Cognitive impairment was de ned as Chinese version of the Mini Mental State Examination score less than 18. Multivariabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
7
25
0
Order By: Relevance
“…We also found that Chinese older adults with both large weight gain and large WC loss were associated with faster cognitive decline. A nationally representative American cohort indicated that a BMI decrease and a WC increase >10% over a 3-year follow-up were related to an increased risk of cognitive decline among older adults (Rodriguez-Fernandez et al, 2017 ), and a recent large cohort study in China reported that large weight loss was associated with an increased risk of cognitive impairment (Wu et al, 2021 ). Losing weight was found to be associated with worse cognitive performance or greater risk of cognitive impairments in later life (Atti et al, 2008 ; Hughes et al, 2009 ; Tolppanen et al, 2014 ; West et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that Chinese older adults with both large weight gain and large WC loss were associated with faster cognitive decline. A nationally representative American cohort indicated that a BMI decrease and a WC increase >10% over a 3-year follow-up were related to an increased risk of cognitive decline among older adults (Rodriguez-Fernandez et al, 2017 ), and a recent large cohort study in China reported that large weight loss was associated with an increased risk of cognitive impairment (Wu et al, 2021 ). Losing weight was found to be associated with worse cognitive performance or greater risk of cognitive impairments in later life (Atti et al, 2008 ; Hughes et al, 2009 ; Tolppanen et al, 2014 ; West et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the baseline information and up to three follow-up assessments to calculate person-specific BMI or WC range at each follow-up for each participant (Capuano et al, 2018 ; Aiken-Morgan et al, 2020 ). In addition, BMI and WC change were classified into 5 groups, namely, large loss (< -10%), small loss (−10 to −5%), stable (−5 to <5%), small gain (5 to <10%), and large gain (more than 10%; Newman et al, 2001 ; Wu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMSE contains a total of 30 items that assess orientation, registration, attention and calculation, recall, and language, with a score range from zero to 30 [ 36 , 37 ]. Use of the MMSE in the CLHLS is well-documented as both reliable and valid [ 22 , 35 , 38 , 39 , 40 , 41 ]. Since MMSE scores might be influenced by education level [ 40 ], participants were defined as cognitively impaired following education-based MMSE cutoff points.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous results suggested that a larger BMI and a BMI-defined overweight status were related to slower cognitive decline [ 13 ]. A cohort study reported that BMI-defined overweight status was associated with a lower risk of cognitive impairment [ 22 ], and another recent cohort study suggested that a BMI-defined underweight status was related to a higher risk of cognitive impairment [ 23 ].…”
Section: Introductionmentioning
confidence: 99%